IMMU-17. USE OF MRNA FOR SAFE AND EFFECTIVE GD2-DIRECTED CAR T CELLS TO TREAT DIFFUSE MIDLINE GLIOMAS. (1st June 2021) - Foster, Jessica; Griffin, Crystal; Stern, Allison; Brimley, Cameron; Storm, Phillip; Barrett, David; Resnick, Adam
Abstract: Chimeric antigen receptor (CAR) T cells targeting the disialoganglioside GD2 have garnered interest as an effective therapeutic for treating diffuse midline glioma (DMG). However, prior studies raised significant concerns of neurotoxicity and fatality when using virally transduced CAR T cells against these midline tumors. Building upon our prior work optimizing mRNA for use in CAR T cells (Hum Gen Ther, 2019), we hypothesized transient GD2-directed mRNA CAR T cells could be successfully employed for safe and effective treatment of DMG. GD2-directed CAR T cells were created using mRNA encoding the 14G2a single chain variable fragment paired with 41BB and CD3-zeta co-stimulatory domains and transfected into human T cells. GD2-directed CAR T cells were tested against a panel of DMG cell lines and two murine xenograft models of DMG: 7316-6349 and SU-DIPG13P*. In all DMG cellular models, GD2-directed mRNA CAR T cells induced significant tumor cell death compared to CD19-directed mRNA CAR T cell controls. In vivo, mRNA CAR T cells were delivered locoregionally using an indwelling infusion catheter to allow for repeated dosing. Four intratumoral doses of 5 x 10 6 GD2-directed mRNA CAR T cells induced significant tumor regression measured by bioluminescence in DMG model 7316-6349 (p<0.0001). In addition, GD2-directed mRNA CAR T cells prolonged survival of mice harboring the aggressive DMG model SU-DIPG13P* by 61% (mean survival 29 days versus 18 days, p<0.01) following four intratumoral doses of 4 x 10 6 CAR T cells. No GD2-directed CAR T cell treatment-related deaths or toxicities were observed. These data highlight the utility of using mRNA to titrate CAR T cell therapy in the brain, and establish GD2-directed mRNA CAR T cells as a safe and effective method for treating DMG.